Analysis of the Prediction when Calculating the Evaporation Rate of an Accidental Liquid Spill during Long Time - Frederic Heymes; Serge Forestier; Clement Chanut (Chemical Engineering Transactions, 2025)
Numerous scientific works aimed a predicting the evaporation rate of a spill in order to predict safety distances during atmospheric dispersion or to calculate the time necessary to evaporate the totality of the spill. Evaporation involves heat and mass balance equations and mass transfer dynamics estimates. A number of parameters have to be estimated: what is the surface of the spill? What is the wind velocity? What is the soil temperature? What is the liquid thickness? What is the initial liquid temperature? This work aimed at estimating the key parameter which will influence the actual rate of evaporation, and to quantify the sensitivity of the existing models when doing an error on the initial parameters estimate. It is demonstrated that both experiments and models doesn’t give the same importance on the parameters. On an another point of view, a mistake on initial parameters will influence the evaporation rate calculation with a changing importance with time: for example, the initial temperature of liquid will influence strongly the evaporation rate calculation at start of evaporation, but will not influence the evaporation rate after a given time (in fact, when the steady state is reached)